2017
DOI: 10.1038/s41598-017-09292-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of varying social experiences during life history on behaviour, gene expression, and vasopressin receptor gene methylation in mice

Abstract: Both negative and positive social experiences during sensitive life phases profoundly shape brain and behaviour. Current research is therefore increasingly focusing on mechanisms mediating the interaction between varying life experiences and the epigenome. Here, male mice grew up under either adverse or beneficial conditions until adulthood, when they were subdivided into groups exposed to situations that either matched or mismatched previous conditions. It was investigated whether the resulting four life hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
2
14
1
Order By: Relevance
“…These neuropeptides signal via their cognate G protein-coupled receptors, arginine vasopressin 1A (Avpr1a) and oxytocin receptor (Oxtr), to modulate diverse aspects of human social behavior, and dysfunction of these systems are well established in neurodevelopmental disorders [17,18,19]. In addition, there is evidence that epigenetic regulation of Avpr1a and Oxtr expression may be particularly sensitive to environmental disruption during critical periods of development [20,21], and post translational modifications to histone tails is one of the major epigenetic processes regulating the transcription of G-protein coupled receptors in the brain [22]. Late prenatal life (e.g., GD 17.5 in the mouse) is one such critical period where we and others have already observed several changes both to fetal physiology [23] and developmental changes to multiple cell types in multiple brain regions [12,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…These neuropeptides signal via their cognate G protein-coupled receptors, arginine vasopressin 1A (Avpr1a) and oxytocin receptor (Oxtr), to modulate diverse aspects of human social behavior, and dysfunction of these systems are well established in neurodevelopmental disorders [17,18,19]. In addition, there is evidence that epigenetic regulation of Avpr1a and Oxtr expression may be particularly sensitive to environmental disruption during critical periods of development [20,21], and post translational modifications to histone tails is one of the major epigenetic processes regulating the transcription of G-protein coupled receptors in the brain [22]. Late prenatal life (e.g., GD 17.5 in the mouse) is one such critical period where we and others have already observed several changes both to fetal physiology [23] and developmental changes to multiple cell types in multiple brain regions [12,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the fetal period, environmental factors have also been found to induce epigenetic changes. For instance, intense social experiences in sensitive life stages can have enduring influences not only on behavior, but also on AVPR1a gene expression in the hippocampal region through a change in patterns of methylation (Bodden et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In adulthood, on the other hand, developmental plasticity is lower due to progressed brain maturation (Rice and Barone, 2000 ). Despite this, however, it has been shown that social experience can still modulate emotional behavior and underlying patterns of gene expression in adult rodents (Buwalda et al, 2005 ; Jansen et al, 2010 ; Bodden et al, 2017 ). In fact, also in the mentioned studies on the “coping with challenge” effect escapable adversity was experienced in early adulthood (Bodden et al, 2015 , 2017 ; Remmes et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, however, it has been shown that social experience can still modulate emotional behavior and underlying patterns of gene expression in adult rodents (Buwalda et al, 2005 ; Jansen et al, 2010 ; Bodden et al, 2017 ). In fact, also in the mentioned studies on the “coping with challenge” effect escapable adversity was experienced in early adulthood (Bodden et al, 2015 , 2017 ; Remmes et al, 2016 ). The results of the present investigation in combination with our previous findings, however, suggest that for the occurrence of the “coping with challenge” effect specific social experiences have to be made already during early phases of life when brain circuits are highly plastic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation